2007
DOI: 10.1016/j.molbiopara.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A plays a crucial role in Giardia lamblia differentiation

Abstract: The ability of Giardia lamblia to undergo two distinct differentiations in response to physiologic stimuli is central to its pathogenesis. The giardial cytoskeleton changes drastically during encystation and excystation. However, the signal transduction pathways mediating these transformations are poorly understood. We tested the hypothesis that PP2A, a highly conserved serine/threonine protein phosphatase, might be important in giardial differentiation. We found that in vegetatively growing trophozoites, gPP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 51 publications
4
47
1
Order By: Relevance
“…However, because we cannot distinguish between old and new discs, it remains possible that the disc fragments in the cyst are derived from the parental disc and are retained as raw material for the construction of new discs during excystation. This is the first study, to our knowledge, to use immunofluorescence staining to examine the Giardia cytoskeleton in depth during excystation, although previous studies have looked at the localizaton of two proteins, PP2A and beta-giardin, in excyzoites (Palm et al, 2005;Lauwaet et al, 2007b). As reported previously (Coggins and Schaefer, 1984;Coggins and Schaefer, 1986;Buchel et al, 1987;Erlandsen et al, 1989), we observed that the excyzoite exits the cyst at one pole, starting with its flagella.…”
Section: Nuclei Are Inherited In Non-identical Pairssupporting
confidence: 73%
“…However, because we cannot distinguish between old and new discs, it remains possible that the disc fragments in the cyst are derived from the parental disc and are retained as raw material for the construction of new discs during excystation. This is the first study, to our knowledge, to use immunofluorescence staining to examine the Giardia cytoskeleton in depth during excystation, although previous studies have looked at the localizaton of two proteins, PP2A and beta-giardin, in excyzoites (Palm et al, 2005;Lauwaet et al, 2007b). As reported previously (Coggins and Schaefer, 1984;Coggins and Schaefer, 1986;Buchel et al, 1987;Erlandsen et al, 1989), we observed that the excyzoite exits the cyst at one pole, starting with its flagella.…”
Section: Nuclei Are Inherited In Non-identical Pairssupporting
confidence: 73%
“…55 ). Interestingly, putative giardial protein homologs of components of the ceramide signaling cascade, including protein phosphatases PP1, PI3K/AKT, and PP2A ( 56 ), are annotated in the Giardia genome database, and the latter was shown to be involved in the differentiation process of the parasite ( 57 ). Thus it is likely that signaling by ceramide, and possibly by other bioactive sphingolipids, is also highly conserved in this simple eukaryote.…”
Section: Resultsmentioning
confidence: 99%
“…Three encystation-specific cyst wall proteins (CWP1, 2 and 3) are expressed and concentrated in encystation-specific-vesicles (ESVs) that circulate within the parasite before being transported to the cyst wall (Luján et al, 1996;Reiner et al, 1990;Lauwaet et al, 2007;Faso and Hehl, 2011;Benchimol and De Souza, 2011). Synthesis of ESVs starts 4-6 h after encystation is induced and is completed with the cyst formation by approximately 24 h (Reiner et al, 1990).…”
Section: Introductionmentioning
confidence: 99%